Innovative geological–geotechnical zoning framework for urban planning: Wuhan’s experience - Lingling He; Yuyong Jiao; You Zhang; Fei Zheng; Hanfa Peng; P. G. Ranjith (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract Traditional methods for understanding geological conditions, such as borehole drilling and on-site tests, are often costly and impractical for extensive urban areas like Wuhan’s Main Urban Area. This study introduces an innovative geological–geotechnical zoning framework that utilizes limited data to overcome these challenges, essential for urban planning, underground space development, and construction design. We began by dividing the study area into four primary geological units based on geomorphological characteristics, using a novel method validated at four metro stations. Our approach incorporated data from 1544 geological boreholes to compile a comprehensive database, from which six typical stratigraphic profiles for each unit were identified. These profiles facilitated the estimation of potential layers and their corresponding geotechnical parameters, and the identification of subsurface hazards. The study resulted in a detailed engineering geological zoning divided into nine secondary units. Our analysis not only demonstrates the effectiveness of the proposed criteria for geomorphological units in achieving more accurate and quantifiable outcomes but also shows the framework’s suitability for regions with complex sedimentary conditions. The resultant engineering geological zoning enhances understanding of geological risks, providing a foundation for safer and more sustainable urban development.